Higher Education System in the Context of Sustainable Development Goals (on the Example of Georgia) - Darchashvili, Manana (Journal of Education Culture and Society, 2022)
Aim. The purpose of the article is to study, analyse and present the readiness of Georgia in the modern period to meet international problems – it is the main goal of sustainable development, including higher education. The government of Georgia, since ancient times correctly understood the role of education for future prosperity, currently the government is doing its best to meet the international challenges in the fourth goal of sustainable development - education, including higher education. Methods. The paper is presented based on official documents, scientific research papers, analysis, and the historical-comparative method. Results. The article presents important challenges for the integration of the Georgian state into the European space at the present stage, which is enshrined in the Constitution (Parliament of Georgia, 2018) and several important documents. In this context, promoting access to education is an important international agreement for the country to overcome modern global challenges - one of the most important goals of sustainable development - an important precondition for strengthening the socio-political and cultural development of society. Conclusion. The paper is based on the study/processing of international and local official materials, as well as expert research has the opportunity to assess the readiness of the higher education system to follow the goals of sustainable development. The country’s relevant structures are actively creating all the conditions for the convergence/engagement of the Georgian educational space under modern international standards which has been demonstrated in practice by the capabilities of higher education institutions.